Understanding rare variant contributions to autism: lessons from dystrophin-deficient model - Claudia Ismania Samogy Costa; Luciana Madanelo; Jaqueline Yu Ting Wang; Gabriele da Silva Campos; Ana Cristina De Sanctis Girardi; Marília Scliar; Frederico Monfardini; Rita de Cássia Mingroni Pavanello; Vivian Romanholi Cória; Maria Dulcetti Vibranovski; Ana Cristina Krepischi; Naila Cristina Vilaça Lourenço; et al. (npj Genomic Medicine)
Abstract Duchenne and Becker Muscular Dystrophy are dystrophinopathies with a prevalence of 1:5000–6000 males, caused by pathogenic variants in DMD. These conditions are often accompanied by neurodevelopmental disorders (NDDs) like autism (ASD; ~20%) and intellectual disability (ID; ~30%). However, their low penetrance in dystrophinopathies suggests additional contributing factors. In our study, 83 individuals with dystrophinopathies were clinically evaluated and categorized based on ASD (36 individuals), ID risk (12 individuals), or controls (35 individuals). Exome sequencing analysis revealed an enrichment of risk de novo variants (DNVs) in ASD-DMD individuals (adjusted p value = 0.0356), with the number of DNVs correlating with paternal age (p value = 0.0133). Additionally, DMD-ASD individuals showed a higher average of rare risk variants (RRVs) compared to DMD-Controls (adjusted p value = 0.0285). Gene ontology analysis revealed an enrichment of extracellular matrix-related genes, especially collagens, and Ehlers-Danlos syndrome genes in ASD-DMD and DMD-ID groups. These findings support an oligogenic model for ASD in dystrophinopathies, highlighting the importance of investigating homogenized samples to elucidate ASD’s genetic architecture.